The New World of the gothic fox : culture and economy in English and Spanish America - Véliz, Claudio (Berkeley : University of California Press, 1994)
The Spanish Indies in the sixteenth and seventeenth centuries was the most prosperous region of the world's greatest secular power. Lofty cathedrals and magnificent municipal buildings rose over Quito, Mexico, Lima, and Potosi at a time when English America consisted of little more than a few scattered settlements. Yet today Latin America is marked by political strife and economic penury while its northern neighbor has become one of the world's most powerful nations. What can explain the divergent historical paths these two bordering regions have taken? In the New World of the Gothic Fox, Chilean Claudio Veliz offers a provocative and original thesis that goes a long way toward answering this question. Veliz adopts the richly suggestive metaphor of foxes and hedgehogs, developed by the Oxford philosopher Isaiah Berlin to describe opposite types of thinker, and applies it to the culture, economic systems, and history of the English- and Spanish-speaking Americas to illuminate the causes of their vast differences. Veliz ranges broadly, covering 500 years of history and returning to the European ancestry of these American peoples to uncover the basis of their varying fates. According to the author, the dominant cultural achievements of England and Spain have been the Industrial Revolution and the Counter-Reformation, respectively. These overwhelming cultural constructions strongly influenced the subsequent historical development of the two nations' cultural outposts in North and South America. The British brought to the New World a stubborn ability to thrive on diversity and change, forged by the Industrial Revolution and reflected in their vernacular Gothic style. Their descendants became the "foxes" of Berlin's metaphor, characteristically independent, pluralistic, and adaptable, qualities that today continue to sustain their technological and scientific prowess. The Iberians, by contrast, brought a cultural tradition represented by the vast baroque dome, a monument to their successful attempt to arrest the changes threatening their imperial moment. The Spanish New World became a society of "hedgehogs," single-minded, systematic, rationalistic. Veliz writes with erudition and wit and brings to bear on his argument a multitude of sources, from the writings of historians and Greek philosophers to modern literature and today's newspaper sports pages. Offering a novel explanation of the prosperity and expanding cultural influence of North American and the economic and cultural decline of South America, this book makes a timely and significant contribution to the fields of Latin American studies, cultural anthropology, and cultural and economic history
Frontmatter -- Contents -- Prologue -- I. Prefatory Metaphors -- II. The Invention of the Indies -- III. The Spanish Counter-Reformation -- IV. Baroque Hedgehogs -- V. Gothic Foxes -- VI. Hellenistic Aftermath -- VII. A World Made in English -- VIII. The Culture of the Latin American Economy -- IX. The Crumbling Dome -- Selected Bibliography -- Index
Includes bibliographical references (pages 231-243) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Latin America -- Civilization -- Spanish influences; North America -- Civilization -- British influences; Comparative civilization; Latin America -- Economic conditions; North America -- Economic conditions; Civilisation comparée.; Amérique latine -- Conditions économiques.; Amérique du Nord -- Conditions économiques.; América Latina -- Civilización -- Influencias españolas.; América Latina -- Condiciones económicas.; América del Norte -- Condiciones económicas.; HISTORY -- General; HISTORY; HISTORY / Europe / General; Civilization -- British influences; Civilization -- Spanish influences; Comparative civilization; Economic history; Latin America; North America; Culturele invloeden; Latijns-Amerika.; Spanje; Noord-Amerika.; Verenigd Koninkrijk van Groot-Brittannië en Noord-Ierland.; Latin America; Regions & Countries - Americas; History & Archaeology; anthropology; baroque mindset; british empire; colonization; counter reformation; cultural achievements; cultural constructions; cultural decline; cultural studies; cultural traditions; culture; economic systems; economics; economy; english america; historical developments; imperialism; industrial revolution; latin american history; modern culture; north america; philosophy; sociology; south america; spanish america; the new world; world history